Media use and brain development during adolescence - Eveline A. Crone (Nature Portfolio, 2018)
The current generation of adolescents grows up in a media-saturated world. Here, Crone and Konijn review the neural development in adolescence and show how neuroscience can provide a deeper understanding of developmental sensitivities related to adolescents’ media use.